Poisedness for social innovation: The genesis and propagation of community- based palliative care in Kerala (India) - Devi Vijay and Philippe Monin (Indian J Psychol Med, 2018)
Background: Suicides rank high as the cause of human deaths. But research on whole family ending life is scanty. This study explored the family suicides in Kerala. Methodology: All the family suicides reported from four central districts of Kerala State during the year 2000 were included. Cases were prospectively located from different sources. A research associate systematically gathered information, from survivors, family and key persons in the locality. Results: 84 lives lost in 32 incidents involving 99 persons. No report from Muslim dominated district. Largest age group was 19 and below, others progressively decreased. Poisoning formed most frequent method; drowning, burns, hanging and wrist slashing followed. Suicide notes were left in half. Mental illness and physical illness were noted in five and eight incidents respectively. Financial crisis reported as the main reason. The SES of the deceased and their parents were same but half of the families were leading a life at a higher level than could be afforded. Warning signals noted in 12 incidents. Decision was taken by father and mother (17), mother (10) or father alone (5).The incidents came to the attention of others without long delay. Discussion: Firm stand of the religion against suicides on individual reasons could explain absence of family suicides from Muslim dominated district. Selection of sure method and flawless execution explains high lethality. Presence of victims explains more loss of young lives and profile difference from reported suicide attempts. Opening up of avenues for higher dreaming due to globalisation and wider visual media could be a reason for living unaffordable standard of life and resulting financial difficulty. The warning signals were recognised, but not responded by others. Social support was strong within the family but was non-existing with outside. Strong social support could be pathological if it is narrow.